Race-Related Differences Between and Within Sex to Experimental Thermal Pain in Middle and Older Adulthood: An Exploratory Pilot Analysis - Karen O. Moss (Frontiers Media S.A., 2021)
This brief report details a pilot analysis conducted to explore racial differences in pain sensitivity and unpleasantness between cognitively healthy Black and White adults, stratified by sex. A total of 24 cognitively healthy adults (12 Black and 12 White) from two completed studies were matched by age and sex, and divided into two groups based on race. Stratified analyses by sex demonstrated that Black females reported experiencing pain intensity ratings of all three intensity sensations at lower temperatures than White females. These findings will inform future research studies to determine if these results hold true in a fully-powered sample and should include mixed methodologies, incorporating neuroimaging data to further assess this phenomenon. Improving pain assessment and management across racial/ethnic groups will help healthcare providers such as nurses and physicians to ensure optimal quality of life for all.